Dydaktyka literatury wobec nowych zadań szkoły = Literary Didactics in View of New School Problems - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The review presents the more important problems of literary didactics context with educational reforms in Poland and with social transmutations caused by the technological revolution. Substantiating the new for qualitative changes in the theory and practice of teaching and learning literature, the author shows the necessity of accepting a practicable strategy in guiding those changes. From this point of view he broadly engages in problems representing the objective of teaching and learning literature, of preparing curricula and the structure of text-books for teachers and pupils.
Keywords: dydaktyka literatury; szkolnictwo